2013
DOI: 10.1158/0008-5472.can-12-4586
|View full text |Cite
|
Sign up to set email alerts
|

Gankyrin Activates IL-8 to Promote Hepatic Metastasis of Colorectal Cancer

Abstract: Hepatic metastasis is responsible for the majority of colorectal cancer (CRC)-related mortalities. Although Gankyrin (PSMD10) has been implicated in cancer metastasis, its exact role and underlying mechanisms of CRC hepatic metastasis remain largely unknown. Herein, we showed that the expression of Gankyrin was higher in primary CRC with hepatic metastasis compared with CRC without metastasis. RNAi-mediated silencing of Gankyrin expression in highly metastatic human CRC cells impaired their migratory and metas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…In several tumor types, including lung, colon and breast cancer, the expression of IL-8 is elevated in tumor tissues compared with normal tissues (20,21). In agreement with these results, the present study revealed that IL-8 is highly expressed in RCC compared with normal tissues (Fig.…”
Section: Il-8 Is Highly Expressed In Rccsupporting
confidence: 90%
“…In several tumor types, including lung, colon and breast cancer, the expression of IL-8 is elevated in tumor tissues compared with normal tissues (20,21). In agreement with these results, the present study revealed that IL-8 is highly expressed in RCC compared with normal tissues (Fig.…”
Section: Il-8 Is Highly Expressed In Rccsupporting
confidence: 90%
“…Gankyrin is a chaperone of the ubiquitin-proteasome and a novel oncogene, and has been demonstrated to be overexpressed in numerous types of cancer (25)(26)(27), including liver cancer (28)(29)(30), breast cancer (31,32), colorectal cancer (33), estrogen-driven endometrial carcinoma (26) and oral cancer (34). Gankyrin serves an essential role in tumor occurrence and development (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). p115 is a tether protein that has an important role in a number of signaling pathways required for cell proliferation, and has been extensively studied (35,36).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hepatic JNK-activation and inflammation may play a crucial role in the progression and development of hepatocellular cancer (HCC) [60,61] as well as chemotherapy resistance of HCC cells [62,63]. Moreover, hepatic inflammation and expression of IL-8 have been shown to promote hepatic metastasis of several types of cancers [64,65]. Therefore, it is intriguing to speculate whether our findings may also have impact on progression and chemotherapy (resistance) of primary and secondary liver cancer, which needs to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%